2002
DOI: 10.1002/ajmg.10603
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for linkage of liability to autism toHOXA1in a sample from the CPEA network

Abstract: A recent study by Ingram et al. [2000b: Teratology 62:393-405] suggests a (His)73(Arg) polymorphism (A:G) in HOXA1 contributes substantially to a liability for autism. Using 68 individuals diagnosed with Autism Spectrum Disorders, they found a significant dearth of G homozygotes and biased transmission of G alleles from parents to affected offspring, especially from mothers. Because the connection between HOXA1 and liability to autism is compelling, we attempted to replicate their finding using a larger, indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
0
16
1
1
Order By: Relevance
“…259,260 Evidence from family studies in human populations has suggested that HOXA1 is associated with genetic susceptibility for autism, 261,262 although results have been inconsistent. 263,264 A HOXA1-related disorder, Bosley-Salih -Alorainy syndrome, has been identified in a small patient sample, with symptoms that include delayed maturation and autism. 265 Gene expression profiles in normal and Hoxa1 À/À embryonic stem cells have shown that Hoxa1 regulates expression of Bdnf and other genes important for development.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…259,260 Evidence from family studies in human populations has suggested that HOXA1 is associated with genetic susceptibility for autism, 261,262 although results have been inconsistent. 263,264 A HOXA1-related disorder, Bosley-Salih -Alorainy syndrome, has been identified in a small patient sample, with symptoms that include delayed maturation and autism. 265 Gene expression profiles in normal and Hoxa1 À/À embryonic stem cells have shown that Hoxa1 regulates expression of Bdnf and other genes important for development.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…182 One group found aberrant forms of HOXA1 and HOXB1 in a survey of autistic families, 179 but this was contradicted by additional studies. [183][184][185] This does not rule out the involvement of other Hox genes as causes of autism, however. Manning et al 186 reported a lower ratio of second to fourth digit length in families with autism, possibly reflecting derangement of prenatal testosterone levels as a result of mutations in HOXA13 or HOXD13.…”
Section: Hypothesis Driven Studies: the Search For Candidate Genesmentioning
confidence: 99%
“…[197][198][199][200][201][202][203] HOXA1 has been shown to play a role in hindbrain development in the mouse model. 204 The first positive finding 196 was not replicated despite similar or better power in most studies.…”
mentioning
confidence: 99%